2010
DOI: 10.1103/physrevlett.104.256803
|View full text |Cite
|
Sign up to set email alerts
|

Surface Band-Gap Narrowing in Quantized Electron Accumulation Layers

Abstract: An energy gap between the valence and the conduction band is the defining property of a semiconductor, and the gap size plays a crucial role in the design of semiconductor devices. We show that the presence of a two-dimensional electron gas near to the surface of a semiconductor can significantly alter the size of its band gap through many-body effects caused by its high electron density, resulting in a surface band gap that is much smaller than that in the bulk. Apart from reconciling a number of disparate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
73
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 28 publications
15
73
0
3
Order By: Relevance
“…This causes the conduction band states to become quantized into two-dimensional subbands (the electron accumulation can be seen as a two-dimensional electron gas (2DEG)). This two-dimensional electronic structure at the surface of CdO has been observed directly by angle-resolved photoemission spectroscopy [150,151], as shown in Fig. 9.…”
Section: Surface Conductivitymentioning
confidence: 94%
See 2 more Smart Citations
“…This causes the conduction band states to become quantized into two-dimensional subbands (the electron accumulation can be seen as a two-dimensional electron gas (2DEG)). This two-dimensional electronic structure at the surface of CdO has been observed directly by angle-resolved photoemission spectroscopy [150,151], as shown in Fig. 9.…”
Section: Surface Conductivitymentioning
confidence: 94%
“…In addition to this Moss-Burstein shift, which widens the optical energy gap, it has been found that many-body interactions lead to a shrinkage of the fundamental band gap with increasing free-carrier concentration [183]. This has been employed in the analysis of optical absorption in many TCOs [184][185][186][187][188][189], and has recently been shown to have a pronounced depth-dependent effect on the band gap size within their surface electron accumulation layers [150], as mentioned above. However, the origins of such band gap narrowing have also recently been questioned [190], with hybridization between states from the dopant impurity atoms and the host conduction band states rather than many-body interactions between the free carriers attributed as the cause of the bandgap shrinkage.…”
Section: Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis of the Hall resistance using the two channels model, we find that the H-induced increase of the electron density is negligible and that the surface accumulation layer has an electron sheet density of $10 16 m À2 , significantly smaller than for In(AsN). Furthermore, whereas in InAs the charge is located on the surface thus leading to a bending of the bands and the formation of two-dimensional (2D) accumulation layer, 16 in In(AsN), the spatially uniform density of donors across the thin ($100 nm) subsurface region of the epilayer and large electron sheet density lead to a 3D electron gas near the surface (Figure 3(c)). …”
mentioning
confidence: 99%
“…In addition, the LDA+U scheme can approximately describe the effect of electron correlation, which may significantly affect the electronic properties of 2DEG. 15,25 An U − J of 10 eV was used for the La f orbitals to push them far from the Fermi level, avoiding the spurious hybridization between them and the Ti d orbitals. The SrTiO 3 (001) surfaces were modelled into a supercell which consists of a SrTiO 3 slab and a vacuum region of about 12 Å.…”
mentioning
confidence: 99%